2009
DOI: 10.1053/j.gastro.2009.05.001
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-analysis Shows That Prevalence of Epstein–Barr Virus-Positive Gastric Cancer Differs Based on Sex and Anatomic Location

Abstract: Background & Aims Epstein-Barr virus (EBV) has been causally associated with cancer; some gastric carcinomas have a monoclonal EBV genome in every cancer cell, indicating that they arose from a single infected progenitor cell. However, the proportion of EBV-positive gastric carcinomas is uncertain and the etiological significance is unknown. Methods We conducted a meta-analysis of 70 studies including 15,952 cases of gastric cancer assessed by in situ hybridization for EBV-encoded small RNA. Results The po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

41
365
5
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 410 publications
(421 citation statements)
references
References 63 publications
41
365
5
10
Order By: Relevance
“…7 It has been suggested that the profound global DNA effects are responsible for the distinctive clinicopathologic features of EBV gastric cancers 20 including male predominance 9,30 and proximal location. 31 Notably, the purported younger age has not been confirmed by recent analysis. 19,32 In the current study, we confirmed the non-antral location.…”
Section: Discussionmentioning
confidence: 90%
“…7 It has been suggested that the profound global DNA effects are responsible for the distinctive clinicopathologic features of EBV gastric cancers 20 including male predominance 9,30 and proximal location. 31 Notably, the purported younger age has not been confirmed by recent analysis. 19,32 In the current study, we confirmed the non-antral location.…”
Section: Discussionmentioning
confidence: 90%
“…LELC constitutes only 1-4 % of all GCs [2][3][4] and has been described as having a favorable prognosis compared with that of ordinary GC, especially in LELCs with Epstein-Barr virus (EBV) infection [1,[5][6][7][8][9]. EBV infection is found in more than 80 % of LELC cases, and EBVpositive LELCs share the following features with EBVassociated GCs: male predominance, predisposition to the proximal part of the stomach, and a high proportion of diffuse-type gastric carcinomas [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…However, the Prevalence rates of EBV in gastroesophageal cancer vary between 5 and 20%, which may depend on the patient groups in different studies [16][17][18]. EBV-associated tumori-genesis appears to be rather restricted to gastric cancer while the role of EBV in other parts such as esophageal carcinomas appears to be insignificant in most parts of the globe [19]. To the best of our knowledge there no study investigated the role of the EBV in the etiology of EC from Sudan.…”
Section: Discussionmentioning
confidence: 85%